2014
DOI: 10.1007/s00339-014-8767-7
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterization of Li insertion in individual silicon nanowires

Abstract: The lithiation and delithiation process of silicon nanowire arrays (SiNWs) on silicon substrates has been studied with high-resolution electron microscopy. The composition of lithiated SiNWs was revealed, consisting of the unreacted crystalline silicon core and the reacted amorphous Li-Si shell. In particular, the Li-Si shell was comprised of a mixture of amorphous silicon oxide and crystalline silicon, leading to hindrance during Li-Si alloying/dealloying upon cycling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…This investigation has permitted to better understand the role of the crystalline-amorphous core-shell structure of the SiNWs on the charge and discharge processes. In particular, as described above, while the reversible process can be attributed to the lithiation of crystalline Si, the high irreversible capacity (70%) found in the first cycle can be ascribed to the formation of a SEI passivation layer on the silicon nanowire surface, induced by the reduction of the electrolyte [48,49]. Some authors showed that a carbon coating or a conductive polymer used as a binder can drastically reduce this irreversible loss [36,37].…”
Section: And 3(b) and Figures 3(c) And 3(d)mentioning
confidence: 91%
“…This investigation has permitted to better understand the role of the crystalline-amorphous core-shell structure of the SiNWs on the charge and discharge processes. In particular, as described above, while the reversible process can be attributed to the lithiation of crystalline Si, the high irreversible capacity (70%) found in the first cycle can be ascribed to the formation of a SEI passivation layer on the silicon nanowire surface, induced by the reduction of the electrolyte [48,49]. Some authors showed that a carbon coating or a conductive polymer used as a binder can drastically reduce this irreversible loss [36,37].…”
Section: And 3(b) and Figures 3(c) And 3(d)mentioning
confidence: 91%
“…Π˜Π·Π²Π΅ΡΡ‚Π½ΠΎ, Ρ‡Ρ‚ΠΎ ΠΏΡ€ΠΈ элСктрохимичСском Π²Π½Π΅Π΄Ρ€Π΅Π½ΠΈΠΈ лития Π² кристалличСский ΠΊΡ€Π΅ΠΌΠ½ΠΈΠΉ ΠΎΠ±Ρ€Π°Π·ΡƒΡŽΡ‚ΡΡ Π°ΠΌΠΎΡ€Ρ„Π½Ρ‹Π΅ сплавы Li x Si ΠΈ послС экстракции лития Si остаСтся Π°ΠΌΠΎΡ€Ρ„Π½Ρ‹ΠΌ [7][8][9]. Как Π±Ρ‹Π»ΠΎ ΠΏΠΎΠΊΠ°Π·Π°Π½ΠΎ Π² [10,11], кристалличСскиС ΠΊΡ€Π΅ΠΌΠ½ΠΈΠ΅Π²Ρ‹Π΅ микроструктуры способны Ρ€Π°Π±ΠΎΡ‚Π°Ρ‚ΡŒ Π² Ρ€Π΅ΠΆΠΈΠΌΠ΅, ΠΊΠΎΠ³Π΄Π° Π»ΠΈΡ‚ΠΈΠΉ ΠΏΡ€ΠΎΠ½ΠΈΠΊΠ°Π΅Ρ‚ Π½Π΅ Π½Π° всю Π³Π»ΡƒΠ±ΠΈΠ½Ρƒ Si-частиц, Ρ‚. Π΅. ΠΏΡ€ΠΈ Ρ†ΠΈΠΊΠ»ΠΈΡ€ΠΎΠ²Π°Π½ΠΈΠΈ cохраняСтся Π³Ρ€Π°Π½ΠΈΡ†Π° ΠΌΠ΅ΠΆΠ΄Ρƒ Π°ΠΌΠΎΡ€Ρ„Π½Ρ‹ΠΌ ΠΈ кристалличСским ΠΊΡ€Π΅ΠΌΠ½ΠΈΠ΅ΠΌ. ΠŸΠ΅Ρ€Π²Ρ‹Π΅ Ρ†ΠΈΠΊΠ»Ρ‹ литирования ΠΈ дСлитирования ΠΈΠ³Ρ€Π°ΡŽΡ‚ Π²Π°ΠΆΠ½ΡƒΡŽ Ρ€ΠΎΠ»ΡŒ для ΠΏΠΎΡΠ»Π΅Π΄ΡƒΡŽΡ‰Π΅Π³ΠΎ повСдСния элСктродов, Ρ‚Π°ΠΊ ΠΊΠ°ΠΊ ΠΎΠΏΡ€Π΅Π΄Π΅Π»ΡΡŽΡ‚, ΠΊΠ°ΠΊΠΎΠ΅ количСство c-Si ΠΌΠΎΠΆΠ΅Ρ‚ Π±Ρ‹Ρ‚ΡŒ ΠΏΡ€Π΅ΠΎΠ±Ρ€Π°Π·ΠΎΠ²Π°Π½ΠΎ Π² Π°ΠΌΠΎΡ€Ρ„Π½Ρ‹ΠΉ.…”
unclassified